(3GdbhGYO GdEbJUGOjI aj EfTGA hJWhjQ GdeOf GdLOjOI (B/s - (3WdYJ, EHQGgjes ((3GdbGgQI(B: s (3OGQ GdcJGH GdMOjK(B, s, 2011)
(3JGQjN hOhGaY GfTGA GdeOf GdLOjOI(B- (3eaghe GdeOf GdLOjOI aj GWGQ SjGSI GdeLJeYGJ GdYeQGfjI GdLOjOI(B- (3GdbGYOI GdEbJUGOjI hGdfeh GdScGfj ddeOf GdLOjOI(B- (3GdMLe GdGeKd ddeOjfI GdLOjOI(B- (3Jehjd GSJKeGQGJ GdeOf GdLOjOI(B- (3GWGQ fXQj dOQGSI LOhi GfTGA GdeOf GdLOjOI(B- (3HQfGeL GfTGA GdeOf GdLOjOI aj LeghQjI eUQ GdYQHjIs
(3GdeQGLY U(B.333s
Keywords: (3GdEbJUGOs; (3GdJNWjW GdEbJUGOjs; (3GdJfejI GdEbJUGOjIs